AN ANALYSIS OF PSYCHOLOGICAL IMPACT ON JUVENILE DELINQUENCY IN JK.ROWLING’S THE CASUAL VACANCY (2012) - Rachayu, Imma; Aprilia, Laura (JURNAL LITERARY CRITICISM, 2015)
The purpose of this analysis is to find out about how the influence of the Id, Ego and Super Ego of the teenage characters in the novel and to know that there is a kind of juvenile delinquency in the novel The Casual Vacancy (2012) Sigmund Freud. Theory about the condition of the human psyche is one theory which is often used, this theory helps in analyzing the psychological condition of a person in the face of the challenges of life in adolescents. By using qualitative descriptive methods the authors tried to explore any form of juvenile delinquency by Fagan (2006). Then the writers also delve more deeply about the psychological impact of juvenile delinquency by Sigmund Freud's theory that the id, ego and super ego. After analyzing the data, which in getting various quotations within the novel, the writers ultimately conclude that the dominant juvenile delinquency, are the use of cigarettes and drugs. Adolescent mental condition is always influenced by the presence of the id, ego and super-ego as it had been by Sigmund Freud describe through the theory of psychoanalysis. Juvenile delinquency largely influenced by his ego. It can be seen from the surrounding adolescent measures contained in the novel The Casual Vacancy (2012). The impact of juvenile delinquency itself will affect himself like any other people around. Keywords: Juvenile Delinquency, Adolescent, The Casual vacancy, Psychoanalytic theory